Women with Heart Failure Are at High Psychosocial Risk: A Systematic Review of How Sex and Gender Influence Heart Failure Self-Care - Jody R. Thomas; Alexander M. Clark (Cardiology Research and Practice)
To improve patient support, it is important to understand how people view and experience Heart Failure (HF) self-care. This systematic review of qualitative studies included all published studies that examine the influence of sex and gender on HF self-care. A systematic search was done for papers (1995–2010) indexed in Ovid MEDLINE, Ovid Medline, Ovid EMBASE, Ovid PsycINFO, CSA Sociological Abstracts, OVID AARP Ageline, EBSCO Academic Search Complete, EBSCO CINAHL, EBSCO SocINDEX, ISI Web of Science: Social Sciences Citation Index and Science Citation Index Expanded, and Scopus. After screening of 537 citations, six qualitative studies identified that differences existed in perceptions of symptoms with women having less family involvement and psychosocial support around self-care. Moreover, women had considerably more negative views of the future, themselves and their ability to fulfill social self-care roles. Women with HF represent a highly vulnerable population and need more support for psychosocial wellbeing and self-care.